Pelatihan Higiene, Sanitasi, dan Keselamatan Kerja untuk Meningkatkan Mutu Produksi Es Batu di UD Frozen Ice - Aulia Brilliantina; Mohammad Mardiyanto; Findi Citra Kusumasari; Muhammad Ihsan Alfarizi; Degita Fami Brillyansyah; Mokhamad Fatoni Kurnianto; Yulia Rachmawati (Abdi Jaya : Jurnal Pengabdian Indonesia, 2025)
UD Frozen Ice is a small-scale enterprise engaged in the production of ice tubes located in Kaliwates District, Jember Regency. As a food product widely used in restaurants and beverage outlets, the safety and quality of ice cubes are strongly influenced by the implementation of hygiene, sanitation, and occupational safety practices during production. Initial observations indicated that personal hygiene, environmental sanitation, and the use of personal protective equipment (PPE) at UD Frozen Ice were still suboptimal, posing potential risks of microbiological contamination and work accidents. This community service program aimed to improve workers’ knowledge and skills in applying hygiene, sanitation, and occupational safety standards. The methods included material dissemination, hands-on training, and evaluation through pre-test and post-test assessments. Results showed an average improvement of 41% in workers’ knowledge after training. In addition, behavioral changes were observed, such as the implementation of routine cleaning schedules, more consistent use of PPE, and the application of safe working procedures in ice tube production. This training program had a positive impact on improving the quality and safety of ice products produced by UD Frozen Ice. Therefore, the program can serve as a model for empowering small-scale food enterprises to enhance hygiene, sanitation, and occupational safety standards in support of food safety and business sustainability.